2017
DOI: 10.1016/j.combustflame.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling PAH curvature in laminar premixed flames using a detailed population balance model

Abstract: A detailed population balance model, which includes the kinetic Monte Carloaromatic site (KMC-ARS) model for detailed polycyclic aromatic hydrocarbon (PAH) growth, is used to compute the Gauss curvature of PAHs in laminar premixed ethylene and benzene flames. Previous studies have found that capping of an embedded 5-member ring causes curvature in graphene edges. In this work, a capping process is added to the KMC-ARS model with the rate coefficient of the capping reaction taken from the work of You et al. [Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…This amount of pentagon integration is higher than the values 28-49% found previously for mature carbon particulates. 26,33 These lower values can be explained by the age of the particles; indeed, the fringe analysis for carbon particulates sampled from the late stages of the flame have considerably flatter and longer fringes, indicating a carbonization process leading to removal of embedded pentagonal rings.…”
Section: Resultsmentioning
confidence: 99%
“…This amount of pentagon integration is higher than the values 28-49% found previously for mature carbon particulates. 26,33 These lower values can be explained by the age of the particles; indeed, the fringe analysis for carbon particulates sampled from the late stages of the flame have considerably flatter and longer fringes, indicating a carbonization process leading to removal of embedded pentagonal rings.…”
Section: Resultsmentioning
confidence: 99%
“…Recent high resolution transmission electron microscopy (HRTEM) studies have shown that significant fractions of aromatic molecules in soot contain non-hexagonal rings [5,6]. Curvature analysis of the fringes using geometrical [5] and statistical models of the curvature [7] showed that the majority of fringes contained a single inflection point indicating pentagon integration, with 28-49% of the fringes containing curvature indicating >1 pentagon. The range of pentagon integration was predicted to span 1-3 pentagons.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the primary particle model and the KMC-Aromatic Site (KMC-ARS) model [41,42] for PAH growth, Kraft and co-workers have developed more detailed population balance models for soot by considering the detailed composition (i.e. PAHs) of soot particles [25,36,37,41,42,[45][46][47]. These models describe soot particles as aggregates composed of primary particles, which are in turn composed of individual PAHs, rather than just carbon atoms as in previous soot models.…”
Section: Introductionmentioning
confidence: 99%